Investigation of a dendrimer-like arrangement of hydrazone fragments for the application as hole transporting materials. Issue 42 (21st October 2015) - Kolesnicenko, Aleksandras; Malinauskas, Tadas; Kasparavicius, Ernestas; Send, Robert; Gaidelis, Valentas; Jankauskas, Vygintas; Wonneberger, Henrike; Bruder, Ingmar; Getautis, Vytautas
Abstract: A new type of dendrimer-like hydrazone hole transporting materials have been reported and their thermal, optical, electrochemical and photophysical properties are investigated and applicability in construction of hybrid solar cells is evaluated. It was found that hole mobility in these hydrazones reaches respectable 2.5×10 −3  cm 2  V −1  s −1 at strong electric fields, which puts them on a par with majority of the best performing amorphous, solution-processed hole transporting materials used today. Graphical abstract: